Immune Checkpoint Inhibitors Remodel the Immune Microenvironment in Brain Metastases and Promote T Cell Infiltration. (16th November 2020) - Kienzler, Jenny C; Lee, Alexander; Reynosi, Jeremy; Kim, Won; Liau, Linda M; Hugo, Willy; Prins, Robert M
Abstract: INTRODUCTION: Each year there are ∼10 times as many brain cancer patients diagnosed with a metastatic brain tumor than with a primary brain tumor. METHODS: We used quantitative multiplex immunofluorescence (IHC), cytometry by time of flight (CyTOF), nanoString® oligonucleotide arrays and single cell RNA sequencing (scRNA) to gain a better understanding of the immune cell phenotypes in ICI naive and ICI treated BM compared with ICI naïve and ICI treated recurrent GBM (RGBM). RESULTS: Multiplex immunofluorescence showed an immune exclusionary phenotype in untreated melanoma, lung and breast BM with an accumulation of CD45 cells in the tumor stroma vs. tumor parenchyma. Expression of PDL1+ on tumor cells and on CD45 cells was higher in breast and lung BM compared to melanoma. Characterization of isolated tumor-infiltrating lymphocytes and myeloid cells by CyTOF revealed a predominance of myeloid cells in ICI naive BM. With ICI treatment before surgery there was a significant increase in T cells preferentially in tumor parenchyma compared with tumor stroma, with a concomitant change in the ratio of T cells to tumor associated macrophages (TAM). Investigation of the activation state of T cells in ICI treated BM by CyTOF, and scRNA revealed an increase in activated effector memory (EM) subsets compared with ICI naïve BM, including T cells that expressed multiple activation/exhaustion markers. In contrast, there were fewer highly activated TEM cells in RGBM cases treated preoperatively with ICI. The frequency of HLA-DR+ myeloid cells increased in ICI treated BM, whereas the frequency of PDL1+ and CD206+ myeloid cells was decreased compared with ICI naïve BM. CONCLUSION: We conclude that ICI treatment in BM alters the immune microenvironment causing a change from one which is immune exclusionary to one characterized by diffuse infiltration of T cells into the tumor parenchyma, an inversion of the T cell: TAM ratio and a change in myeloid cell phenotypes. It appears that these effects are more pronounced in ICI treated BM than in ICI treated RGBM, and support the further exploration of neoadjuvant ICI as a therapeutic modality for brain metastases.